Obesity as Risk Factor for Acute Coronary Disease in Al-Mosul City in Iraq: A Cross-Sectional Study: Obesitas sebagai Faktor Risiko Penyakit Koroner Akut di Kota Al-Mosul, Irak: Sebuah Studi Cross-Sectional - Aziz Alfhadl, Nabil Hamdallah; Khader, Younis Mohmad; Zaid, Zaid Ahmed; Ibrahim, Khalid Ramadhan (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Acute coronary syndrome represents a group of cardiac disorders that mainly occur due to a sudden reduction of the blood supply of the heart. This occurs when an atherosclerotic plaque ruptures withing the coronary arteries. Several risk factors are associated with the occurrence of ACS that can be classified as modifiable and non-modifiable risk factors. Prevention of more heart damage and mitigating the unfortunate consequences are crucial. Aim of Study: This research aims to identify the possible associations between obesity, lipid profile, and the risk of experiencing ACS in a specific geographic region (Al-Mosul City, Iraq). Methodology: This cross-sectional study was performed in Mosul City, Iraq, in 2025, this study provided data from 50 participants who were chosen according to s strict criteria including individuals experiencing obesity at any age and sex, people with a history of cardiovascular diseases, inherited cardiac disorders, and metabolic abnormality status. Data collection was adhered to under the supervision of the medical professional. Data included demographic data, laboratory investigation, and clinical measurement of the weight and height. Analysis was performed using Jamovi 2.4.1.0. Results: This study provided significant data about the risk factors that are affecting obese individuals to the possibility of having ACS, elevated BMI, and dyslipidemia was observed among participants, which raises the suspicion of experiencing ACS in the future. Conclusion: Obesity and dyslipidemia represent a serious healthcare problem worldwide, They are significant contributors to ACS risk. This study aims to identify these risk factors in Mosul City, Iraq, and to prevent further complications. Highlights: ACS is triggered by plaque rupture, with modifiable and non-modifiable risk factors. Investigate obesity, lipid profile, and ACS risk in Mosul, Iraq. Obesity and dyslipidemia significantly contribute to ACS risk, requiring preventive measures.. Keywords: Acute Coronary Syndrome, Obesity, Lipid profile, Cholesterol, Triglycerides, HDL, VLDL, LDL.